2014
DOI: 10.1016/j.yexcr.2014.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin-A associates with histones intracellularly and shuttles them to exosomes to promote focal adhesion assembly resulting in rapid adhesion and spreading in breast carcinoma cells

Abstract: The present analyses were undertaken to define the mechanisms by which fetuin-A modulates cellular adhesion. FLAG-tagged fetuin-A was expressed in breast carcinoma and HEK-293T cells. We demonstrated by confocal microscopy that fetuin-A co-localizes with histone H2A in the cell nucleus, forms stable complexes with histones such as H2A and H3 in solution, and shuttles histones to exosomes. The rate of cellular adhesion and spreading to either fibronectin or laminin coated wells was accelerated significantly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 39 publications
(68 reference statements)
1
51
0
Order By: Relevance
“…These two groups of EV share similarities on the molecular level, therefore it has been suggested that MV are membrane-anchored exosomes (47, 69). In our studies, histone 3a, which has been reported to be present in exosomes (70, 71), was also detected in MV (Fig. 4B).…”
Section: Discussionsupporting
confidence: 79%
“…These two groups of EV share similarities on the molecular level, therefore it has been suggested that MV are membrane-anchored exosomes (47, 69). In our studies, histone 3a, which has been reported to be present in exosomes (70, 71), was also detected in MV (Fig. 4B).…”
Section: Discussionsupporting
confidence: 79%
“…We previously demonstrated that fetuin‐A in the extracellular milieu promotes rapid uptake of exosomes by cultured tumor cells . In the present studies, we questioned whether exosomal uptake is attenuated in fetuin‐A knocked down glioblastoma cells.…”
Section: Resultsmentioning
confidence: 69%
“…In order to directly implicate histones and fetuin‐A in the uptake mechanisms of hydroxyapatite‐nanoparticles, we reasoned that fetuin‐A which has a high affinity for hydroxyapatite and also associates with positively charged histones could theoretically load histones on hydroxyapatite‐nanoparticles much the same way that it loads histones on exosomes. When fetuin‐A was mixed with the nanoparticles resulting in FN to which cells were added in the wells of 96‐well microtiter plates, the uptake of the particles by PC3 and DU145 cells was negligible (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously proposed that histones/fetuin‐A were the exosomal ligands that interact with cell surface heparan sulfate proteoglycans. These two proteins were abundantly associated with a class of exosomes that were easily taken up by tumor cells . This observation, however, did not rule out the other exosome‐associated proteins such as CD63 and other tetraspanins .…”
mentioning
confidence: 89%
See 1 more Smart Citation